Traditional resources and tools for modern drug discovery: Ethnomedicine and pharmacology – book review - Salam, Muhamad Elfitra; Anshori, Khoiruddin; Lessy, Nina Sakina; Purnama, Sri Yuli (Ethnobotany Research and Applications, 2025)
This book provides innovative insights into the combinatorial use of plant-based compounds for drug discovery and development to achieve improved treatment outcomes. It explores the evolution of ethnobotany and traditional medicine as the foundation for modern drug development, employing biotechnological methods that involve the identification, screening, and optimization of natural compounds to enhance affinity, selectivity, bioavailability, and metabolic stability. The book also highlights the crucial role of bioactive compounds in contemporary pharmaceutical research, specifically examining how drugs influence the molecular and physiological regulation of infections and diseases. Written by leading experts and supported by up-to-date literature and illustrations, this volume serves as a valuable academic resource for researchers, industry professionals, and health policymakers.